2021
DOI: 10.1108/meq-11-2020-0245
|View full text |Cite
|
Sign up to set email alerts
|

Green product preferences considering cultural influences: a comparison study between Malaysia and Indonesia

Abstract: PurposeThere is an increasing awareness among manufacturers to make production more sustainable in Southeast Asian countries such as Malaysia and Indonesia. Manufacturers are now urged to not only focus on the business profit but also concern on environment protection by producing green products. However, issues may arise regarding the preferences of customers on green products, which will vary due to the influence of cultural values. This will give an impact on the marketing of green products. The aim of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 89 publications
0
15
0
Order By: Relevance
“…However, the absence of the negative effect of authoritarian leadership on OCB and individual creativity could be attributed to the cultural differences. In Malaysia, there is a high power distance and therefore expecting obedience at workplace does not always have a negative effect on employees' behavior (Ghazali et al, 2021). Pizzolitto et al (2022) reported that authoritarian leadership does not affect employee performance when applied in settings where a power distance is high.…”
Section: Discussionmentioning
confidence: 99%
“…However, the absence of the negative effect of authoritarian leadership on OCB and individual creativity could be attributed to the cultural differences. In Malaysia, there is a high power distance and therefore expecting obedience at workplace does not always have a negative effect on employees' behavior (Ghazali et al, 2021). Pizzolitto et al (2022) reported that authoritarian leadership does not affect employee performance when applied in settings where a power distance is high.…”
Section: Discussionmentioning
confidence: 99%
“…By considering its stronger influence, Malaysia has adopted the 2030 Agenda for Sustainable Development at the United Nations General Assembly (UNGA) on 25 th September 2015 in New York (Yusof et al, 2020). One of Malaysia's commitment to the Sustainable Development Goals (SDG) strategy is to be more responsible in the production and consumption stages (Ghazali et al, 2021). The government provides financial incentives for green technology and renewable energy to optimize the use of resources to produce sustainable products and encourages industries to evaluate their environmental impact-related activities during the production stage (Chua et al, 2019;Ghazali et al, 2021).…”
Section: Problem Statementmentioning
confidence: 99%
“…One of Malaysia's commitment to the Sustainable Development Goals (SDG) strategy is to be more responsible in the production and consumption stages (Ghazali et al, 2021). The government provides financial incentives for green technology and renewable energy to optimize the use of resources to produce sustainable products and encourages industries to evaluate their environmental impact-related activities during the production stage (Chua et al, 2019;Ghazali et al, 2021). However, the challenge is the stage of consumption by consumers in Malaysia (Ghazali et al, 2021;Suki, 2016).…”
Section: Problem Statementmentioning
confidence: 99%
See 2 more Smart Citations